Foundations of library and information science - Rubin, Richard E., 1949-; Rubin, Rachel G.; Alire, Camila A. (Chicago : ALA Neal-Schuman, 2020)
"This edition has been designed to respond to the many changes occur ring in the LIS field and provides a firm foundation of knowledge and g uidance for LIS students and professionals alike"--
The knowledge infrastructure -- From past to present : the history a nd mission of libraries -- The library as an institution : an organizat ional perspective -- Transforming the library : the impact and implicat ions of technology -- Library and information science : an evolving pro fession -- The organization of knowledge : techniques and issues -- Inf ormation science : a service perspective -- Information policy : stakeh olders and agendas -- Intellectual freedom -- The values and ethics of library and information science -- Appendix A. Major library and inform ation science associations and list of additional associations -- Appen dix B. List of ALA-accredited programs -- Appendix C. Standards for acc reditation of master's programs in library and information studies -- A ppendix D. IFLA/UNESCO public library manifesto 1994.
Includes bibliographical references and index.
Keywords: Library science -- United States; Information science -- United States